PENGARUH PENDIDIKAN, PELATIHAN TEKNIS KEUANGAN DAN PENGALAMAN KERJA TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Pada SKPD Provinsi Sulawesi Tengah) - Hartati, Hartati (Katalogis, 2016)
This research aims to determine and analyze the simultaneous and partial influences of educations, finances technical training, and work experiences on the quality of financial report in Central Sulawesi. The test result show that education, finance technical training, and work experiences simultaneously have significant influence on the quality of financial report in Central Sulawesi by conducting f-test with R2 of 0,670. In other words, 67% of independent variable is influenced by the independent variables; the remaining is influenced by other variables that are not included in the study. Education significantly influences the quality of financialÂ report with t value of 0,276; financial technical training significantly influences the quality of financial report with t value of 0,166; work experience significantly influences the quality of financial report with tvalue of 0,255.